Influence of brick and mortar properties on bioreceptivity of masonry – Results from experimental research. (10th January 2021) - Lubelli, B.; Moerman, J.; Esposito, R.; Mulder, K.
Highlights: Moisture transport of brick-mortar combination is crucial for bioreceptivity. The composition of the mortar strongly affects its bioreceptivity. Lime-trass and, in lower extent, NHL binders show the best bioreceptivity. A compromise is needed between bioreceptivity and mechanical strength. Abstract: The effect of mortar and brick properties on the growth of ivy-leaved toadflax ( Cymbalaria muralis ) and yellow corydalis ( Pseudofumaria lutea ) has been investigated in laboratory. Different mortar compositions were designed and tested in combination with two different bricks. Highly porous bricks and mortars showed good bioreceptivity; mortars with lime-trass and, in lower extent, those with natural hydraulic lime binder, gave the best results in terms of bioreceptivity. The addition of vermiculite to the mortar was beneficial for plant growth. The brick-mortar combinations most favourable for plant growth were those with estimated low compressive and flexural bond strength values. Proposals are advanced for obtaining a compromise between mechanical strength and bioreceptivity.